FISH ASSEMBLAGES IN NON‐REGULATED AND REGULATED RIVERS FROM PERMANENT AND TEMPORARY IBERIAN SYSTEMS. (5th July 2012) - Alexandre, C. M.; Ferreira, T. F.; Almeida, P. R.
ABSTRACT The effects of river regulation on the hydrological cycle of a river and on the respective fish assemblage may differ according to dam operation purpose and type of river analysed. To assess the spatial and temporal variation of fish assemblages and their response to the hydrological changes caused by two different types of flow regulation, we selected three sampling sites in four rivers with different levels of regulation, two in a permanent river system and another two on a temporary one, which we sampled in four different annual seasons. In the permanent system, hydroelectrical regulation decreased hydrological variability, which affected fluvial specialist species, benefitting the generalist ones, and created a more homogeneous community that presented less intra‐annual variation. In the temporary system, agricultural regulation caused an inversion of the hydrological cycle, maintaining a moderate flow volume throughout the drought period that benefited the introduced, generalist and more tolerant species. Monthly volume was recognized, in a temporal scale, as the most important hydrological feature for assemblages' structure, predicting the intra‐annual variation of several ecological guilds. This study provides important considerations for dam management and riverine ecosystems conservation. Copyright © 2012 John Wiley & Sons, Ltd.